Ultrasound-triggered doxorubicin targeted delivery for liver cancer treatment: Reduced toxicity and improved efficacy - Remya Radha; Shabana Anjum; Rand Hasan Abusamra; Vinod Paul; William G. Pitt; Ghaleb A. Husseini; Mohammad H. Al-Sayah (PLoS ONE, 2026)
Liver cancer, especially hepatocellular carcinoma (HCC), remains a major global health challenge, causing high mortality worldwide. Conventional chemotherapy often results in severe side effects due to its systemic distribution, which limits its effectiveness in targeting cancer cells specifically. The development of targeted drug delivery systems can enhance the precision and efficacy of chemotherapeutic agents while reducing their side effects. In this context, we used lactobionic acid (LA) as a targeting moiety due to its ability to bind to the asialoglycoprotein receptor (ASGPR), which is highly expressed on the surface of hepatocytes (liver cells). Conjugating lactobionic acid to liposomes creates an efficient delivery system that specifically targets liver cancer cells, thereby ensuring a higher uptake of the drug by these cells. Ultrasound is used to further facilitate drug release by enhancing drug targeting, promoting accumulation at the tumor site, and triggering drug release, thereby making the treatment more effective and less toxic. This study successfully synthesized stable DOX-loaded liposomes conjugated with lactobionic acid (LL) on their surface, with a size range of 89.4 ± 0.9 nm and a polydispersity index of 13.06 ± 3.5. Successful LA-DSPE-PEG-NH 2 conjugation to the LL was confirmed via Fourier Transform Infrared spectroscopy. The sulfuric acid colorimetric assay quantified lactobionic acid conjugation as 14 ± 1.35% (w/w), while DOX encapsulation was measured at 40.1 ± 1.6%. LL exhibited strong absorption, fluorescence properties and good stability at 37 ˚C. LL showed controlled release via ultrasound, making it suitable for precise drug delivery. In vitro studies on HepG2 cells confirmed enhanced drug uptake and therapeutic efficacy. The effects of ultrasound-enhanced drug delivery to HepG2 cells demonstrated that the combination of ultrasound and targeted liposomes significantly increased the internalization of the drug (DOX) and triggered apoptosis in HepG2 cells, leading to cell death. Morphological observations on treated cells via phase contrast microscopy supported the signs of apoptosis, indicating LL’s potential to target liver cancer cells effectively.